Educational television and the extent to which it applies comprehensive quality standards in Arabic language lessons for the sixth literary class (Journal of the College of Basic Education, 2023)
The current research aims to find out (to what extent educational television applies comprehensive quality standards in the Arabic language lessons offered to the finished classes). The research community consisted of the Arabic language lessons presented by the Iraqi educational television for the sixth literary grade for the academic year (2021-2022), which numbered (27) lessons, and the researcher chose (all vocabulary of the research community) as a sample for his research. The researcher prepared an observation card for analyzing the lessons, consisting of (55) indicators distributed in (5) fields, and presented it in the form of a questionnaire to the specialists, arbitrators, and experts. to verify its authenticity. The researcher adopted two methods to verify the stability of the observation card, the first (agreement over time), and the other (agreement with another observer), after the researcher chose a sample of (20%) for stability, as the number of the sample of stability was (13) lessons. The researcher used the statistical methods: Pearson correlation coefficient; , weighted mean, and weight percentile. And among the most prominent findings of the research: The Arabic language lessons on television were characterized by quality in four fields, and were not characterized by quality in one field, which is (the field of television directing for the Arabic language lesson). And through the results, the researcher concluded: The lessons provided have plans that organize their presentation and cover the educational material with appropriate time periods. The quality he prepared for evaluating TV Arabic lessons, or TV lessons for other educational subjects.